2013
DOI: 10.1074/jbc.m113.456178
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of Cultured Neonatal Cardiomyocytes by Plasmalemmal Versus Intracellular G Protein-coupled Receptor 55

Abstract: Background:The LPI-sensitive receptor GPR55 signals through Ca 2ϩ . Results: Activation of sarcolemmal versus intracellular GPR55 mobilizes Ca 2ϩ from distinct pools and associates with cardiomyocyte depolarization and hyperpolarization, respectively. Conclusion: GPR55 location critically affects LPI-induced modulation of cardiomyocyte function. Significance: We identify GPR55 as a new receptor regulating cardiac function at two cellular sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 75 publications
3
40
0
Order By: Relevance
“…We note that the significant effects of LPI observed in this study occurred at concentrations of 1 and 10 mM, which are well in the range of tissue concentrations that can be reached in pathophysiological states in vivo (Shen et al, 2001;Xiao et al, 2001;Sutphen et al, 2004;Ross, 2011) and largely similar to those promoting cellular effects in vitro (Falasca et al, 1995;Lauckner et al, 2008;Yu et al, 2013). Brain concentration of lipids, and implicitly, LPI, are difficult to evaluate due to limitations in extraction procedures, specificity, and rapid degradation.…”
Section: Functional Role Of Gpr55 In the Periaqueductal Graymentioning
confidence: 72%
See 4 more Smart Citations
“…We note that the significant effects of LPI observed in this study occurred at concentrations of 1 and 10 mM, which are well in the range of tissue concentrations that can be reached in pathophysiological states in vivo (Shen et al, 2001;Xiao et al, 2001;Sutphen et al, 2004;Ross, 2011) and largely similar to those promoting cellular effects in vitro (Falasca et al, 1995;Lauckner et al, 2008;Yu et al, 2013). Brain concentration of lipids, and implicitly, LPI, are difficult to evaluate due to limitations in extraction procedures, specificity, and rapid degradation.…”
Section: Functional Role Of Gpr55 In the Periaqueductal Graymentioning
confidence: 72%
“…We and others previously reported that LPI-induced activation of GPR55 is associated with Ca 21 signaling in neurons and other cell types (Lauckner et al, 2008;Pineiro and Falasca, 2012;Yu et al, 2013). Ca 21 responses in PAG neurons may differentially impact modulatory pain signals originating in this brain region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations